Project communication from start to finish the dynamics of organizational success - Hynes, Geraldine E. (Portfolio and project management, 2019)
Chapter 1. Introduction to project communication -- Chapter 2. Communication cornerstones -- Chapter 3. Formal interpersonal communication -- Chapter 4. Informal interpersonal communication -- Chapter 5. Project success in a global context